Methodological aspects of pH and EC measurements in geothermal water - Kmiecik, Ewa; Wątor, Katarzyna; Tomaszewska, Barbara; Sekuła, Klaudia; Mika, Anna (Bulletin of Geography. Physical Geography Series, 2019)
A proper methodology for collecting samples of geothermal water makes it possible not only to determine the hydrochemical characteristics of the water, but also to assess its temporal and spatial variability. The knowledge about the concentration of selected elements as well as the values of field measurements can help to indicate their impact on other environments and the processes that occur in a geothermal system. An important issue is the quality of the results obtained from in-situ measurements of unstable parameters, i.a. pH and electrical conductivity (EC). The results of measurements presented in the paper were completed with the use of three different devices in hot and cooled raw geothermal water (field test). The research was performed during two seasons of increased (winter) and lower (summer) exploitation of geothermal water. The percentage difference between EC at temperatures of 22ºC and 75ºC was 3.27%; however, for the pH the observed percentage difference was only 0.26%. An additional experiment was carried out on a laboratory scale to indicate the influence of temperature changes on pH and EC measurements.